Constructive feedback in the development of written and research communicational skills in two generations of medical students in Yucatan, Mexico - Aguilar Vargas, Esteban (2016)
Background. Research and written communication skills are essential in undergraduate medical education, because medical doctors are often involved in research, and written communication is part of a medical doctor´s everyday routine. Academic medical programs that include training in clinical or epidemiological research require written communication aptitudes. Constructive feedback is a review technique commonly employed in medical education that involves the professor´s close surveillance of the student’s performance and a clear communication to respectfully explain to students their strengths, weaknesses and opportunities of improvement, while ensuring a fair evaluation. Even though constructive feedback is common in clinical practice, it is rarely used in undergraduate medical training in scientific writing. Objective. To evaluate the impact of constructive feedback on the academic performance of students in their clinical or epidemiological research protocol proposals, involving written and methodological aspects. Design. Analytical, prospective study. Setting. Universidad Marista de Mérida, Yucatán, México. Participants. Students in their fourth year of medical education. Intervention. The quantitative evaluations obtained in the research protocol proposals before and after the constructive feedback were compared in 103 students in their fourth year of medical education who were attending the Clinical and epidemiological Research Methods course during 2014-2015 and 2015-2016 school years. Results. The mean of the initial score was 8.3 ± 0.8, and the mean post constructive feedback was 9.4 ± 0.9; the average score increase was 1.1 ±0.10 with t=7.70 value, p=0.000. Students improved the following communication skills: 1. Theme presentation and review, 2. Organization of a scientific manuscript, 3. Use of written language, and 4. Use of information sources. Conclusion. There was a significant improvement in protocol proposals following provision of constructive feedback reviews to students, both in written and methodological aspects.